Community Empowerment Through Waste Management in Sukajaya Village RW 04 - Nirvana, Tri Adi; Avianty, Ichayuen (Universitas Ibn Khaldun, 2023)
Garbage has become a classic problem in every environment, in the city and in the village. Lack of knowledge and public concern for the environment is one of the causes of waste accumulation. The provision of counseling on how to process waste aims to make the community aware of the dangers of waste for health and know how to manage useful waste. The method used is the survey method to Sukajaya Village RW04. Through breastfeeding attended by 42 people, they were able to decompose the accumulation of organic waste and anorgnik waste. The result of the evaluation after the activity was completed was that the community's behavior was now more concerned about the environment and health, it was seen that there was very little garbage scattered around in the Sukajaya village environment.